2018
DOI: 10.3390/catal8110509
|View full text |Cite
|
Sign up to set email alerts
|

Probing Active Sites on Metal-Free, Nitrogen-Doped Carbons for Oxygen Electroreduction: A Review

Abstract: The Metal-free nitrogen-doped carbons represent an emerging low-cost nonprecious electrocatalyst for oxygen reduction reaction (ORR) that is a sluggish process at the cathode of polymer electrolyte membrane fuel cells (PEMFCs) and a verity of metal-air batteries. During the past few years, the ORR catalytic activity of nitrogen-doped carbons has been significantly increased, making them highly competitive alternatives to conventional precious metals based electrocatalysts for ORR. However, controversies remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…The specifications for a fuel cell system consist of establishing the performance, dimension, weight and size, emissions, output power, rapid start-up, and rapid response to changes in load, lifetime, and operability in intense environments and noise, which play an important role in certain applications. Great attention has been paid to replacing platinum group metals with carbon-based non-precious metal, nanoporous metals [ 333 , 334 , 335 ], heteroatom-doped carbons [ 336 ], covalent organic frameworks [ 337 , 338 ], non-precious metal, or precious-metal-free catalysts of inexpensive metals [ 339 , 340 , 341 ] as a promising new generation of electrocatalysts has emerged. This is due to their reduced cost, enhanced performance, and high stability and activity of fuel cell applications.…”
Section: Performance Of Single Monocells—pemfcsmentioning
confidence: 99%
“…The specifications for a fuel cell system consist of establishing the performance, dimension, weight and size, emissions, output power, rapid start-up, and rapid response to changes in load, lifetime, and operability in intense environments and noise, which play an important role in certain applications. Great attention has been paid to replacing platinum group metals with carbon-based non-precious metal, nanoporous metals [ 333 , 334 , 335 ], heteroatom-doped carbons [ 336 ], covalent organic frameworks [ 337 , 338 ], non-precious metal, or precious-metal-free catalysts of inexpensive metals [ 339 , 340 , 341 ] as a promising new generation of electrocatalysts has emerged. This is due to their reduced cost, enhanced performance, and high stability and activity of fuel cell applications.…”
Section: Performance Of Single Monocells—pemfcsmentioning
confidence: 99%
“…Since graphitic‐N is more stable than pyridinic‐N, pyrrolic‐N and oxidized‐N during the second heat treatment in N 2 , it can be inferred that compared with N‐C850‐900, more pyridinic‐N and pyrrolic‐N have been removed from N‐C800‐900 by the post‐treatment process. It has been reported that besides pyridinic‐N, graphitic‐N can also strongly influence the ORR activity according to the literature 25,46,54 . It was supposed that Gibbs' free energy change of the first‐electron reduction proceeded on carbon atoms contiguous to graphitic‐N is much slower than the one surrounding pyridinic N or pyrrolic N, which makes graphitic‐N more efficient 54 …”
Section: Resultsmentioning
confidence: 99%
“…Many low-cost and efficient catalysts have been developed, including transition metals and nitrogen co-doped carbons (M-N/C, M=Fe or Co) [25], metal oxides [37], transition metal carbides [38], nitrides [39], and metal-free heteroatom-doped carbon-based catalysts [40]. Compared to metal-contained catalysts, the heteroatom-doped carbon-based materials with N, S, B, and P, can promote oxygen adsorption on the carbon nanostructure since these hetero-atoms are more electronegative than carbon, and cause neighboring carbon atoms electron deficiency [41]. Among them, N-doped carbons are extensively studied due to their remarkable ORR catalytic activity.…”
Section: Improving Orr and Oermentioning
confidence: 99%